2021
DOI: 10.3390/s21144726
|View full text |Cite
|
Sign up to set email alerts
|

IMUMETER—A Convolution Neural Network-Based Sensor for Measurement of Aircraft Ground Performance

Abstract: The paper presents the development of the IMUMETER sensor, designed to study the dynamics of aircraft movement, in particular, to measure the ground performance of the aircraft. A motivation of this study was to develop a sensor capable of airplane motion measurement, especially for airfield performance, takeoff and landing. The IMUMETER sensor was designed on the basis of the method of artificial neural networks. The use of a neural network is justified by the fact that the automation of the measurement of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…It is shown that the identification accuracy of HDNN is the best and the hazard identification accuracy can be improved by the HDNN which was proposed. Pytka et al [18] presented the development of the IMU-METER sensor which was designed for measuring the aircraft's ground performance and also to study the aircraft movement's dynamics. To develop a sensor for the measurement of airplane motion, airfield performance, etc.…”
Section: Literature Surveymentioning
confidence: 99%
“…It is shown that the identification accuracy of HDNN is the best and the hazard identification accuracy can be improved by the HDNN which was proposed. Pytka et al [18] presented the development of the IMU-METER sensor which was designed for measuring the aircraft's ground performance and also to study the aircraft movement's dynamics. To develop a sensor for the measurement of airplane motion, airfield performance, etc.…”
Section: Literature Surveymentioning
confidence: 99%
“…MEMS gyroscopes and MEMS accelerometers are commonly used in aeronautical applications. Characteristic examples of such applications are presented in the works [1][2][3][4][5]. Because of their small size, they are the only possible choice for small UAVs [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Sci. 2024, 14, x FOR PEER REVIEW 2 of 23 applications are presented in the works [1][2][3][4][5]. Because of their small size, they are the only possible choice for small UAVs [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The practical use of an electric discharge in a liquid for destruction (crushing, grinding, and dispersion) has significantly outstripped the study of the theoretical foundations of the mechanism of electrohydraulic destruction of materials. This was also facilitated by the fact that for a long time the action of an electrohydraulic discharge was completely identified with the action of explosives, but several important factors inherent only in an electrohydraulic discharge were not taken into account [37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%